The effects of fiscal policy shocks on the business environment - Dobrotă, Gabriela; Voda, Alina Daniela; Dumitrașcu, Dănuț Dumitru (Journal of Business Economics and Management, 2021)
Fiscal policy influences economic conditions through public spending and taxes, generating positive or negative impulses, both on short and long term. The present research focuses on analysing the effects of the discretionary changes in the fiscal policy in seven post-communist countries of the European Union during the period 2000–2018. The autoregressive distributed lag model (ARDL) has been applied in order to obtain the convergence rates to equilibrium with a clear analysis of the periods needed to achieve the long-run fiscal sustainability. Also, the error correction vector model (VECM), which is based on the autoregressive vector (VAR) model, has been used in the second part of the analysis focusing on the Cholesky factorization of innovations. Impulse-response functions aiming to estimate the response of government expenditures to the shock produced by three macroeconomic variables have been identified.